Weed dynamics, grain yield and quality of basmati rice (Oryza sativa) under organic agriculture system - HASAM, HASAMUDDIN; KAUR, SIMERJEET; SHARMA, NEERJA; KAUR, TARUNDEEP; AULAKH, CHARANJIT S; BHULLAR, MAKHAN S (The Indian Journal of Agricultural Sciences, 2021)
There is a growing demand for organically produced food including basmati rice (Oryza sativa L.) worldwide and organic farming is continuously gaining importance. The objectives of study were to manage weeds in organically grown basmati rice with non-chemical weed management approaches including tillage, plant density and green manuring. The two year experiment was conducted at Punjab Agricultural University, Ludhiana during summer (kharif) of 2017 and 2018. The combinations of conventional tillage (CT) or deep tillage (DT) with green manure levels at 50, 75 and 100 kg/ha plus 25% higher plant density and one hand pulling including one weedy check and weed-free treatment were studied for weed control in basmati rice. The lowest weed density and biomass was observed in plots with green manuring at 100 kg/ha. Weed density was statistically similar in weed control treatments including CT or DT with green manuring at 50-100 kg/ha plus 25% higher plant density along with one hand pulling and it was significantly lower than weedy check. Crop growth, yield attributes and grain yield was found statistically similar in non-chemical weed management treatments and conventional agriculture treatment. Different quality parameters such as physical and milling properties of paddy and eating and cooking parameters of milled rice grains were statistically similar in differential tillage, green manuring and plant density treatments. Thus, weeds in organically grown-basmati rice may be controlled by using green manuring and higher plant density.